2009
DOI: 10.1007/s11845-008-0271-7
|View full text |Cite
|
Sign up to set email alerts
|

Potential impact of enhanced practice efficiency on endoscopy waiting times

Abstract: Maintaining timely access to endoscopic services is becoming more challenging in the face of growing demand. Modifications in routine clinical practice can significantly impact procedure waiting times. In an era where economic aspects of medical care are becoming increasingly important and where there is growing focus on waiting times as a measure of clinical performance, these findings underscore the importance of providing clinical care in the most efficient manner possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
1
6
1
Order By: Relevance
“…In the context of endoscopy, we have previously demonstrated that efficiency of practice can be improved by employing personnel to obtain prior intravenous access and consent of patients prior to the procedure and implementing a 2-suite-per-endoscopist model [12], such practice significantly changes the shortening procedure waiting times [13]. Similarly, Zamir and Rex [14] demonstrated room turnover time to be a key determinant of procedure efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of endoscopy, we have previously demonstrated that efficiency of practice can be improved by employing personnel to obtain prior intravenous access and consent of patients prior to the procedure and implementing a 2-suite-per-endoscopist model [12], such practice significantly changes the shortening procedure waiting times [13]. Similarly, Zamir and Rex [14] demonstrated room turnover time to be a key determinant of procedure efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Schoenmeyr et al [35] revealed a sensitive relationship between the caseload (i.e., demand) and the wait time in a congested recovery room. Harewood et al [36] found that annual wait time for routine endoscopic procedures lengthened dramatically because of a significant increase in annual procedure demand on endoscopy services. Therefore, we hypothesize that demand has a positive impact on throughput ( Hypothesis 1 , H1 ) and wait time ( Hypothesis 2 , H2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Trzeciak and Rivers [38] also found that inpatient capacity (e.g., beds) had an effect on the throughput in an emergency department. Harewood et al [36] further showed that modifications in routine clinical practice (i.e., service capacity) could significantly affect a procedure's wait time.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations